Assessing the impact of attachment to primary care and unattachment duration on healthcare utilization and cost in Ontario, Canada: a population-based retrospective cohort study using health administrative data - Fitzsimon, Jonathan; Cronin, Shawna; Gayowsky, Anastasia; St-Amant, Antoine; M. Bjerre, Lise (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Insufficient access to primary care remains a major public health issue in Ontario, Canada, particularly for unattached residents (i.e., those who are not formally enrolled with a primary care provider, usually a family physician or occasionally a nurse practitioner). This study evaluates healthcare utilization and costs among unattached individuals, focusing on the impact of unattachment duration. Methods We conducted a population-based retrospective cohort study using health administrative data, comparing provincially insured residents who maintained a consistent attachment status over the 12-month period (April 1, 2021, to March 31, 2022) to those who were unattached. We employed multivariable regression analyses to examine the associations between attachment status, duration of unattachment, demographic and patient health characteristics, and healthcare utilization and costs. Results Prolonged periods of unattachment to primary care were significantly associated with increased healthcare costs, particularly in populations with a higher burden of comorbidities. In the context of healthcare costs, attached residents with low comorbidities had a median cost of $287, increasing to $3,711 (cost ratio: 12.93, CI: 12.86–13.01, p < 0.0001) for those with high comorbidities. Unattached individuals with low comorbidities had a median cost of $238 (cost ratio: 0.83, CI: 0.82–0.83, p < 0.0001), rising to $7,106 (cost ratio: 24.76, CI: 24.27–25.26, p < 0.0001) for high comorbidities, and up to $8,177 (cost ratio: 28.49, CI: 26.61–30.49, p < 0.0001) for long-term unattached with high comorbidities. Conclusions Our findings underscore the substantial impact of long-term unattachment on both individual patients and the healthcare system, with higher levels of chronic disease further exacerbating these effects. These results are crucial for shaping programs and policies to maximize their impact on reducing emergency department visits, hospitalizations, and overall healthcare costs.